THE DEVELOPMENT OF ACCOUNTING PRINCIPLES. - Sanders, T. H. (The Accounting Review, 1935)
Abstract The editorial in the December issue of the journal The Accounting Review is entirely right in pointing out the importance at this time of a better development of accounting principles. Everybody engaged in accounting work, whether in teaching or practice, has the feeling that this is a crucial era for the profession and all its adherents. The fact that accountants are, as everybody hopes, on the eve of another great expansion of business activity, makes it urgently desirable that business take every step which may help to make the next period of prosperity healthier and more permanent than the last one. The work of the United States Securities and Exchange Commission is bound to have a vital influence in defining and giving effect to accounting principles. But when the editorial referred to uses this situation as a stick with which to beat the accounting profession, chides it for its tardiness and reluctance to submit itself to a prescribed discipline. The editor is entirely right in his primary contention. This matter cannot stand still. The principles, practices, and literature of accounting must be advanced and developed to the point of being more definite, more helpful, to all the interested parties.